A rectal gastrointestinal stromal tumor—a plea for neoadjuvant imatinib and TAMIS - Balu,Jagan (2020)
Abstract Here we describe an infrequent case of gastrointestinal stromal tumor of the rectum in a 57 year-old man with spindle cell neoplasm probably gastrointestinal stromal tumor and CT scan showed tumor from the anterior rectal wall and offered abdominoperineal resection for the same. The patient was started on imatinib and had a significant reduction in symptoms. The patient was reassessed with the CT scan, which showed a reduction in tumor size and Transanal minimally invasive surgery was planned for the patient. Use of imatinib prior to surgical resection to attain the reduced size of the tumor within the limit of resection is an attractive approach. Since tumor development can happen rapidly again after substantial tumor shrinkage, the best time to operate depending on resectability and the maximum therapeutic outcome remains divisive.